A typology of climate-conflicts in the Amazon: A scoping review of the unintended socio-political consequences of climate action and inaction - Medina, Leonardo; Higuera Florez, Julian; Penel, Charlotte; Carneiro, Bia; Tucci, Giulia; Madurga Lopez, Ignacio; Navarrete Frías, Carolina; Bonatti, Michelle; Pacillo, Grazia (2025)
The Amazon biome faces mounting pressures from climate change, land-use transformation, and entrenched socio-political inequalities, creating complex risks for ecosystems, livelihoods, and governance. Projections suggest widespread forest dieback, intensified droughts, and extreme rainfall, with consequences that extend beyond ecological and economic damage to strain institutions and heighten resource competition. This report presents a scoping review of evidence on climate–conflict linkages in the Amazon, examining how both climate action and inaction interact with historical inequalities, governance arrangements, and cultural dynamics. Findings highlight that mitigation and adaptation efforts—particularly forest conservation, renewable energy projects, and infrastructure development—have often generated tensions when imposed through top-down, restrictive, or militarized approaches that marginalize Indigenous peoples and local communities. By contrast, participatory initiatives that respect territorial rights, promote equitable benefit-sharing, and integrate Indigenous knowledge have strengthened cooperation, livelihoods, and trust in governance. Evidence on the consequences of climate inaction remains comparatively sparse, despite clear recognition of how droughts, floods, displacement, and institutional weaknesses intersect with conflict risks. The analysis identifies eleven climate–conflict clusters across the region, organized into four categories: direct and indirect consequences of climate interventions, and direct and indirect consequences of failing to act.